Numerical and experimental study on effects of fuel injection timings on combustion and emission characteristics of a direct-injection spark-ignition gasoline engine with a 50 MPa fuel injection system. (5th November 2018) - Kim, Taehoon; Song, Jingeun; Park, Junkyu; Park, Sungwook
Highlights: High pressure injection up to 50 MPa was adopted for direct-injection spark-ignition gasoline engine. Numerical analysis was carried out to analyze the experimental results. High injection pressure is effective to reduce fuel film formation. Late injection can be used to increase turbulence intensity using 50 MPa injection pressure. Abstract: In this study, an increase in injection pressure was proposed as a solution to the problem of exhaust emissions, such as soot, NOx, CO, HC, in direct-injection spark-ignition gasoline engines. Mixture formation and combustion process were analyzed with KIVA-3V release 2 code. Combustion pressure and emission data were also measured experimentally. To validate the models used in simulation, spray tip penetration for various injection pressures, and combustion pressure for various injection timing and injection pressure combinations were compared with experimental data. The simulation using a constant-tuned models showed reliable results and simulations were carried out using validated models. When the fuel is injected while the intake flow is developing, the mixture homogeneity was reduced and combustion speed decreased. When the fuel is injected after the intake flow has fully developed and injection pressure was high, the combustion speed increased. High injection pressure was effective in increasing the mixture homogeneity in case of late injection timing. Therefore, increasing thermal efficiency without deteriorating exhaust emissions is possible when an injection pressure up to 50 MPa is used with late injection timing.